Analisis Digital Marketing, Testimoni Alumni, Dan Kualitas Customer Service Terhadap Minat Mendaftar - Yaqin, Muhammad Husnul; Mega Hastuti, Sri Wahyuni; Mutiara, Nisa; Mulyaningtiyas, Ratna Dewi (Universitas Islam Kadiri, 2025)
This study aims to determine the effect of digital marketing, alumni testimonials, and customer service quality on interest in registering at SMAN 5 Taruna Brawijaya Kediri. The research method used is a quantitative method with a descriptive approach. Data collection in this study was carried out by distributing questionnaires to students of SMAN 5 Taruna Brawijaya and analyzed using SPSS Version 25. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test, and R2 Determination Coefficient Test. In the Validity Test, it is known that all question items (X1, X2, X3, and Y) have a significance value of 0.000 <0.05, thus each variable is declared valid. Then in the Reliability Test, each variable is declared reliable because it has a Cronbach's Alpha value> 0.60. Then in the t-test, the significance value of the digital marketing variable (X1), alumni testimonials (X2), and customer service quality (X3) was obtained at 0.000 <0.05, which indicates that the three variables partially have a significant effect on interest in registering. Then in the F-test, a significance value of 0.000 <0.05 was obtained, indicating that digital marketing, alumni testimonials, and customer service quality have an effect on interest in registering at SMAN 5 Taruna Brawijaya